Isomer-specific investigation of PCDD/F mobility and other fate processes in deep soil cores. (October 2015) - Grant, Sharon; Stevenson, Gavin; Malcolm, Don; Zennegg, Markus; Gaus, Caroline
Highlights: Deep soil cores (to 20 m) were analysed to assess field mobility and fate of PCDD/Fs. Isomer profiles could differentiate sources and elucidate subsurface fate processes. Facilitated transport of PCDDs in agricultural and other soils was extensive. PCDD profile changes with depth reflected aged-related lateral dechlorination. Substantial unrecognised subsurface PCDD loads may be stored in Queensland soils. Abstract: Polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) are highly hydrophobic compounds with low migration potential in soil–water. Nevertheless, they have been occasionally reported in subsurface soils hypothesised as the result of facilitated transport processes with colloids or surfactants, or yet unidentified in-situ formation processes. To date, however, the prevalence of deep soil contamination, involved processes and their kinetics remain poorly understood. This study investigated PCDD/F concentrations and isomer profiles through deep soil cores (to 20 m) from agricultural, industrial and urban sites in Queensland, Australia. Based on isomer profiles, a unique source common to all core soils (regardless of depth) was identified, dominated by octachlorodibenzo- p -dioxin (OCDD). The source was consistent with contamination resulting from pesticide impurities. Elevated PCDD concentrations (μg/kg range) to depths up to ∼4–17 m and a continuous increase of peri-chlorinated (1, 4, 6, 9-substituted) isomers through the cores suggested that vertical transport and lateral dechlorination were key post-depositional processes at these sites. The mobility of PCDDs in the present study is far greater than previously reported in soils in general. High estimated mass transport rates for OCDD in four agricultural cores (3.0–6.2% year −1 ) likely reflect significant levels of facilitating species, including surfactants, and intensive rainfall at these sites. The implications of such extensive subsurface transport of PCDD/Fs for groundwater contamination and load estimates may be significant. If the cores of the present study are assumed representative of the region, a total PCDD/F load in the order of 800 tonnes (1.6 tonnes TEQ) could be present in subsurface Queensland coastal soils.